SMEs Digitalization: Usage of Accounting Application by Vocational School Students - Suhayati, Ely; Saleha, S; Sanggrahwati, M; Merindha, A E (International Journal of Research and Applied Technology (INJURATECH), 2024)
The purpose of this study is to find out the benefits of using the MYOB Accounting application for students majoring in accounting at Vocational High School Baleendah 3 Bandung, both for those who already have their own business or those who do not have their own business. This research method was descriptive qualitative using Google Form to 17 students majoring in accounting at Vocational High School Baleendah 3 Bandung. The results showed that students majoring in Accounting felt the benefits of using the MYOB Accounting application to run their business to make it easier for them to make financial reports. In conclusion, the use of the MYOB Accounting application can help low-income accounting students, especially to present financial reports quickly, precisely, and accurately for those who already have their own business. For those who do not have their own business, the use of MYOB has the benefit of knowing accounting software to support business while working in the future.